A Study on The Implementation of Building Automation System (BAS) at Government Hospital in Johor - Zul Rashidi, Ahmad Amirul Aiman; Abdul Rahman, Mohd Fahmi (Progress in Engineering Application and Technology, 2022)
This study will discuss the implementation of Building Automation System. A building automation system (BAS) is an intelligent system of both hardware and software, connecting heating, venting and air conditioning system (HVAC), lighting, security, and other systems to communicate on a single platform. This way the automation system is delivering you crucial information on the operational performance of a building as well as enhancing the safety and comfort of the occupants. These systems can play an important role in regular energy monitoring and management and therefore to save the possible energy and cost. The key point of the building automation system is focused upon better facilitation to the user in terms of comfort at reduced operation cost. Energy efficiency improvement will also contribute to environmental protection.